(untitled) (Research, Society and Development, 2020)
This study aimed to assess the economic and commercial performance of the Mangalarga Marchador horse breeding, and production costs in the Rio de Janeiro. Data was collected from the ABCCMM archives and from associated breeders, selected through stratified sampling by the mesoregions of the State of Rio de Janeiro. The main means of marketing the animals is selling on the farm. The average of horse’s sale per stud farm in the Rio de Janeiro is 14.92/year with the average of R16,628.46/horse, generating an estimated sale at the farms of around R192,026,783.88/year. The sale of mating (8.77 mating/year) and weaned foals (5.44 foals/year) contributed to the largest volume of sales at the stud farms. Donor mares (R57,318,908.50) and mares (R42,958,357.20) represented the highest in terms of market value throughout the Rio de Janeiro. The Coastal Lowlands mesoregion had the highest average of animals sold per stud farm/year (40.57 animals) and the Central Fluminense mesoregion had the lowest average (25.39 animals). The average commercialization per farm/year corresponds to R385,667.90 and the average total value traded in the Rio de Janeiro is R465,880,252.32/year. The average is 6.52 hired employees, which is equivalent to an average monthly labor gross cost of R11,286.00. Rio de Janeiro employs around 5,584 people directly, the greatest numbers in the Metropolitan mesoregion (1,833 employees), and the lowest concentration in the Northern Fluminense mesoregion (530 employees). Together with the production costs, Mangalarga Marchador horse’s business turns over more than R650 million per year in the Rio de Janeiro.